Statistical approaches to uncertainty: p values and confidence intervals unpacked. Issue 5 (30th September 2005) - DOLL, HELEN; CARNEY, STUART
Abstract : In a previous Statistics Note, we defined terms such as experimental event risk (EER), control event risk (CER), absolute risk reduction (ARR), and number needed to treat (NNT). 1 Estimates such as ARR and NNT alone, however, do not describe the uncertainty around the results. P values and CIs provide additional information to help us determine whether the results are both clinically and statistically significant (table 1Table 1 ).